Sosyal, siyasî ve dinî yönleriyle Yemen Hûsî Hareketi - (:unkn) unknown (My University, 2011)
Bu çalışma, 2004 yılında başlayan Yemen'deki Hûsî isyanının arkasındaki örgütlü güç olan Hûsî hareketini tarihsel, sosyal, siyasî ve dinî yönleriyle incelemeyi amaçlamaktadır. Yemen ülkesi bu vesileyle sosyo-politik ve sosyo-dinî açıdan güncel bir tahlile tâbi tutulmayı hak et-mektedir. Bu tahlil sadece Hûsî hareketinin tanınmasına bir kapı aralamayacak, buna ilaveten, karmaşık bir sosyal yapıya sahip olan günümüz Yemen'indeki dinî akımlar, sosyal ağları ve siyasî bağlantılarıyla birlikte daha belirgin bir şekilde fark edilmiş olacaktır.

This study aims to examine Yemen Huthi movement, which has been in the state of armed in-surgency against Yemeni government since 2004, with its historical, social, political and reli-gious aspects. On this occasion, Yemen deserves to be subjected to an up-to-date analysis from socio-political and socio-religious perspectives. This analysis does not only open a door to identifying the Zaydiyya-rooted Huthi movement, but also more specifically reveals other reli-gious trends with their social networks and political connections in Yemen which has a complex social and religious structure.
Huthi Movement in Yemen with its social, political and religious aspects